Der Natur und Kunst gewidmet Der Esterházysche Landschaftsgarten in Eisenstadt - Prost, Franz (2001)
The book is based on the research project "The Esterházy Landscape Garden in Eisenstadt" funded by the Jubilee Fonds of the Austrian National Bank (no.5164) and was published with the aid of a printing subsidy granted by FWF. For the first time one of the outstanding historical gardens of Austria is presented in a comprehensive monography. The contributions cover a wide range of topics from aspects of cultural heritage preservation and the history of the shaping of the garden as well as the topochronological analysis of maps and plans by means of historical cartography to an in-depth study of plant history focussing on one of the most famous greenhouse plant collections of the first decades of the 19th century as well as on the varieties of trees and shrubs of the landscape garden itself. According to the outstanding importance of the greenhouses and their plant collections a specific focus is laid upon the exploration of the building history and the species-specific analysis of the collections. A detailed inventory of the historical composition of open ground species of trees and shrubs of the landscape garden provides insight into the stages of the shaping of the garden from a botanical view. This inventory is contrasted with the actual situation in regard to ecological, vegetation-scientific and floristic aspects. The second edition of the book is extended by a study of the formerly landscaped area of the so-called Gloriette (Temple of Mary) which is located outside the garden but represents an integral part of the original concept of a designed landscape. The final chapter serves as a detailed guide to the connoisseur by describing an annotated walk through the garden enriched by a wealth of remarks of general historical, of literary and plant-historical as well as garden-historical background.